Improving Students Critical Thinking Ability Through MABER Media (Multimedia Form of Interactive Energy) in Elementary School - Lungdiansari, Nevananda Arica; Riswari, Lovika Ardana; Sekar Dwi Ardianti (Jurnal Pijar Mipa, 2024)
This research was conducted because there are learning activities that do not use learning media, especially technology-based; teaching materials still only use books, and still use the lecture method, causing students to get bored easily, and less interested when learning material is explained, causing a lack of knowledge, apart from critical thinking skills. students are still relatively low. The aim of this research is to improve students' critical thinking skills through MABER, which is the learning media used in this research. This interactive multimedia contains material examples of energy and energy changes in everyday life, media in science and technology subjects in grade IV SDN 05 Ngasem Batealit Jepara. This research uses the Pre Experimental Designs type, with a research design namely One Group Pretest-Posttest. Non-test data collection techniques include observation and interviews and test techniques in the form of pretest and post-test questions. The data analysis technique uses the N-Gain test to determine the increase in students' critical thinking by giving pretest and post-test questions with MABER media. Improving the critical thinking abilities of class IV students through MABER media was carried out through One Group Pretest-Posttest research by giving questions according to critical thinking indicators before and after using MABER learning media. The aim was to determine the increase in students' critical thinking abilities. The results of the pretest and posttest were tested using the N-Gain test. This research showed an increase in the critical thinking skills of class IV students by 0.60 in the medium category. In conclusion, the existence of MABER (Interactive Multimedia in the Form of Energy) media has succeeded in improving the critical thinking skills of fourth-grade elementary school students.